2004
DOI: 10.1021/bi0481489
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Is the Major Physiological Activator of Lecithin−Cholesterol Acyltransferase (LCAT) on Apolipoprotein B Lipoproteins

Abstract: Our previous studies have indicated that lecithin-cholesterol acyltransferase (LCAT) contributes significantly to the apoB lipoprotein cholesteryl ester (CE) pool. Cholesterol esterification rate (CER) in apoA-I(-)(/)(-) apoE(-)(/)(-) mouse plasma was <7% that of C57Bl/6 (B6) mouse plasma, even though apoA-I(-)(/)(-) apoE(-)(/)(-) plasma retained (1)/(3) the amount of B6 LCAT activity. This suggested that lack of LCAT enzyme did not explain the low CER in apoA-I(-)(/)(-) apoE(-)(/)(-) mice and indicated that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 49 publications
4
30
0
2
Order By: Relevance
“…In addition, removal of the apoE resulted in a loss of ability of HDL to promote cholesteryl ester accumulation suggesting that apoE may play a key role. Other studies suggest that apoE has an important role as an LCAT activator in mouse apoB lipoproteins [275]. In an x-ray crystal model of apoE bound to phospholipids, it has been suggested that apoE molecule was folded into half in a belt-like manner around a spheroidal phospholipid molecule, forming a circular horseshoe two helices thick and one helix wide but not a complete belt [276].…”
Section: Abcg1mentioning
confidence: 99%
“…In addition, removal of the apoE resulted in a loss of ability of HDL to promote cholesteryl ester accumulation suggesting that apoE may play a key role. Other studies suggest that apoE has an important role as an LCAT activator in mouse apoB lipoproteins [275]. In an x-ray crystal model of apoE bound to phospholipids, it has been suggested that apoE molecule was folded into half in a belt-like manner around a spheroidal phospholipid molecule, forming a circular horseshoe two helices thick and one helix wide but not a complete belt [276].…”
Section: Abcg1mentioning
confidence: 99%
“…ApoE at high levels restricts VLDL lipolysis, in part by displacing the lipoprotein lipase activator apoprotein CII from the particle (8). ApoA-I, the premier activator of LCAT, is much less efficient on large HDL particles and apoB-containing lipoproteins where apoE functions as the LCAT activator (9,10). ApoE may also influence the activity of hepatic lipase and cholesteryl ester transfer protein (CETP) (11).…”
Section: Apoe and Plasma Lipoprotein Homeostasismentioning
confidence: 99%
“…Plasma LCAT cholesterol esterification rate (CER) was determined using a modification of the Stokke and Norum procedure [5][6][7] . Briefly, a pooled plasma sample (200 L) was incubated with BSA solution containing 3 10 6 dpm of 3 H-cholesterol on ice overnight.…”
Section: Endogenous Lcat Assaysmentioning
confidence: 99%
“…Type 2 diabetes is an important risk factor for the development of cardiovascular diseases (CVD) 6) and recently, blood glucose level management has been shown to be important in avoiding microvascular and macrovascular complication of diabetes 7,8) . Oral anti-diabetic sulfonylurea agents (SUAs) have been widely used to improve glycemic control.…”
Section: Introductionmentioning
confidence: 99%